2012
DOI: 10.1212/wnl.0b013e318258f75c
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic abnormalities in frontotemporal dementia

Abstract: Saccades are abnormal in FTD, reflecting reduced decision-making speed, and these abnormalities related to atrophy of the left frontal eye field. In addition, patients with FTD had an increased incidence of early saccades, which may be due to reduced inhibition of primitive responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…However this has been found to be both less sensitive and less specific than psychometric testing (Torlot et al 2013). Saccadometry, on the other hand, provides an objective and quantitative measure that has been validated as a marker of cognitive function in a number of other neurological pathologies (Ali et al 2006;Antoniades et al 2010;Burrell et al 2012Burrell et al , 2013Dawson et al 2011;Ghosh et al 2010;Michell et al 2006;Perneczky et al 2011;Roos et al 2006;Temel et al 2009). Moreover, it is comparatively rapid, taking only 7 min to gain a data set, and requires no specialist training or personnel to administer.…”
Section: Discussionmentioning
confidence: 99%
“…However this has been found to be both less sensitive and less specific than psychometric testing (Torlot et al 2013). Saccadometry, on the other hand, provides an objective and quantitative measure that has been validated as a marker of cognitive function in a number of other neurological pathologies (Ali et al 2006;Antoniades et al 2010;Burrell et al 2012Burrell et al , 2013Dawson et al 2011;Ghosh et al 2010;Michell et al 2006;Perneczky et al 2011;Roos et al 2006;Temel et al 2009). Moreover, it is comparatively rapid, taking only 7 min to gain a data set, and requires no specialist training or personnel to administer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in a study comparing FTD (n = 22) and control (n = 23) subjects, saccadic latency was prolonged and early saccades were increased, reflecting increased atrophy of the left frontal eye field and reduced speed of decision making processes. 108 In addition, a study demonstrated that FTD (n = 28) subjects presented abnormalities in reflexive visually guided saccades, as did AD (n = 10) participants. 109 In a smaller size study of FTD associated with motor neuron disease (MND), and in whom gross ocular abnormalities were present, slowing of both vertical and horizontal saccades was observed.…”
Section: Eye Movementsmentioning
confidence: 97%
“…In addition, patients with FTD had an increased incidence of early saccades, which may be due to reduced inhibition of primitive responses. 31 Although FTLD, CBD, and PSP might present with similar pathology, they do represent distinct syndromes. 32 The results of the ocular motor studies so far suggest that saccadic analysis may be useful in differentiating these groups (saccadic gain and velocity, and antisaccade performance).…”
Section: Research Findingsmentioning
confidence: 99%